Effects of deficit drip irrigation at different growth stages on citrus leaf physiology, fruit growth, yield, and water productivity in South China - Fei Chen; Ningbo Cui; Shouzheng Jiang; Wenjiang Zhang; Hongping Li; Xiaomeng Li; Min Lv; Chunwei Liu; Rangjian Qiu; Zhihui Wang (Agricultural Water Management)
Seasonal droughts and extreme weather events are threatening citrus production in south China. Investigating the effect of deficit irrigation (DI) on leaf physiology, fruit growth, yield and crop water productivity (WPc) is significantly important for the sustainable development of citrus industry. In this study, a full irrigation treatment (CK) and 16 DI treatments were designed including the low (LD, 85 %CK), mild (M1D, 70 %CK), moderate (M2D, 55 %CK) and severe (SD, 40 %CK) DI treatments at bud bust to flowering stage (I), young fruit stage (II), fruit expansion stage (III) and fruit maturation stage (IV), respectively. Compared with CK, DI treatments at stage I-IV raised the hydrogen peroxide content by 14.4 %-76.6 %, except for LD treatment. Meanwhile, the activities of superoxide dismutase, peroxidase, catalase and the content of proline also increased by 10.5 %-47.3 %, 24.9 %-77.4 %, 20.2–49.8 % and 10.1 %-39.0 %, respectively, which allowed crop to cope with DI-induced oxidative stress. When stomatal conductance (Gs) at stage I-IV reached 0.030–0.040, 0.074–0.096, 0.204–0.219, and 0.114–0.142 mmol·m−2·s−1, respectively, leaf net photosynthesis rate (Pn) did not significantly change, but transpiration rate was limited, and hereby enhanced instantaneous water use efficiency. In addition, although DI treatments at all stages reduced Pn, they did not always have a negative impact on yield due to the obvious improvement of leaf photosynthesis and fruit growth after re-irrigation. Specifically, re-irrigation after I-M1D, II-M1D and III-LD treatments increased the fruit growth rate at stages II, III and IV, respectively, which could further maintain or even enhance the yield, and improve WPc by 5.6 %-7.0 %, 5.7 %-8.6 % and 3.4 %-4.7 %, respectively. IV-M2D treatment increased WPc by 13.7 %-14.5 %. In summary, DI treatment could regulate Gs and fruit compensatory growth after re-irrigation, respectively, so as to achieving water saving and high yield of citrus. I-M1D, II-M1D, III-LD and IV-M2D treatments was recommended as the suitable deficit drip irrigation pattern to ensure efficient citrus production.